Benefits and inconveniences of the practical implementation of Environmental Life Cycle Costing - Biernacki, Michał (Korzyści i ograniczenia związane z wdrożeniem rachunku ELCC w przedsiębiorstwach, 2018)
Environmental Life Cycle Costing (ELCC) combines life cycle analysis and cost systems applied by managers in order to assess the limitations of environmental production systems. It enables the evaluation of progress in implementing sustainable development by determining the social costs of resource consumption and environmental degradation. This study presents the results of empirical research covering production enterprises with foreign equity participation operating in Poland which have the basic ELCC model in place. The research is aimed to identify the benefits and inconveniences arising from the practical application of the model as a significant factor determining its functioning in entities. The research methodology was supplemented by numerous literature items, analysis of survey questionnaires, as well as deduction and induction methods
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 3, s. 9-16
Keywords: ELCC; costing; green accounting